Enhancement of the ion beam emission in a low energy plasma focus / Lim Lian Kuang - Lim, Lian Kuang (2012)
The characteristic of the plasma focus device as efficient source of ion beam generation as well as X-ray source is particularly an appealing subject of study. In this work, we optimized a plasma focus to work at low pressure as an ion beam source. The plasma focus used is of Mather type which is powered by a low inductance capacitor (15 kV, 30 F). At the discharge voltage of 15 kV, maximum energy supplied to the system is 3.3 kJ. The primary objective of the current project is to to find an optimum condition for ion beam production in deuterium filling. The geometry of the electrodes employed is meant for low pressure operation. Experiments are conducted with deuterium as the working gas at pressure of less than 1 mbar. Operation at this low pressure regime is found to produce much more significant ion beam than at normal pressure of several mbar. The axial current sheath velocity of up to 10 cm/s is achieved, which is near to the speed limit recommended for good focusing discharge. Intense focusing discharge with good reproducibility has been obtained at operating pressure in the range of 0.05 – 0.5 mbar. The energy of the ion beam has been determined using time of flight technique by employing three biased ion collectors installed at the end on direction. Intense ion beam emissions with good reproducibility have been obtained. Optimum operating pressure for the ion beam production is around 0.1 mbar, where the average ion beam energy registered was 80 keV. The average total deuteron flux per shot is estimated to be 2.1 x 1018 cm-2 at 0.1 mbar. The deuteron beam with average energy for the pressure of 0.05 – 0.5 mbar was determined to be in the range of 25 – 80 keV. Correlation of ion beam and X-ray emission as well as other discharge parameters with operating pressures has been investigated. X-ray emission was measured by a filtered 5-channel windowless BPX-65 photodiode array. Soft X-ray production from the plasma focus was also found to be pressure dependent and exhibit similar trend to the ion beam emission. The highest Xray emission is also observed at pressure of 0.1 mbar which implies that high temperature plasma column has been formed. A reliable plasma focus device with consistent high production of ion beam or X-ray emission could be used as ion beam source or light source in various technological fields.